1998
DOI: 10.1021/cr941199z
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan:  Preparation, Structure, Properties, and Applications

Abstract: under Prof. S. Claesson. Holding 24 industrial patents and author of more than 120 publications, he has lectured at several European universities. His current interest is in the photochemistry and physical chemistry of polymers. He is a member of the Czech Chemical Society. Stefaan De Smedt was born in Geraardsbergen, Belgium, in 1967. He studied pharmacy at the University of Ghent, Belgium, and received his M.S. degree in pharmaceutical sciences in 1990. As a scholar of the Belgian Institute for the Encourage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
322
1
13

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 671 publications
(342 citation statements)
references
References 247 publications
6
322
1
13
Order By: Relevance
“…36,37 Because the physico-chemical and biological properties of HA are often dependent on its size, 38 we have sought to investigate these differences in the context of stimulating elastin matrix synthesis. 16,17 In other studies, copper ions (Cu 2þ ) have been shown to minimize vascular defects, 39 promote angiogenesis, 40 and enhance LOX enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Because the physico-chemical and biological properties of HA are often dependent on its size, 38 we have sought to investigate these differences in the context of stimulating elastin matrix synthesis. 16,17 In other studies, copper ions (Cu 2þ ) have been shown to minimize vascular defects, 39 promote angiogenesis, 40 and enhance LOX enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is a linear polysaccharide composed of a repeating disaccharide unit of N-acetyl-D-glucosamine and D-glucuronic acid bound by β 1,4 glycosidic bond. The disaccharides are linked by β 1,3 bonds to form the hyaluronic acid chains (Lapcík L Jr and et al, 1998). In vivo, hyaluronate exists as a polyanion rather than its protonated form, hyaluronic acid, although the terms are often used synonymously in the literature (Liao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its degradation rate and the diffusion of active molecules through it can be modulated by selecting a specific range of molecular weights, or by using different crosslinking agents and fabrication procedures. Furthermore, HA induces a low inflammatory response and may contribute to neovascularization through its lowmolecular weight oligomers [32,38,39]; in addition, it can be functionalized variously to improve cell adhesion, proliferation, migration and differentiation [40,41]. For all these reasons, HA seems a promising material for nerve and brain tissue repair [32,[39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%